Physical parameters of components in close binary systems. I - Kreiner, J. M.; Rucinski, S. M.; Zola, S.; Niarchos, P.; Ogloza, W.; Stachowski, G.; Baran, A.; Gazeas, K.; Drozdz, M.; Zakrzewski, B.; Pokrzywka, B.; Kjurkchieva, D.; et al. (Astronomy and Astrophysics, 2003)
The paper presents combined spectroscopic and photometric orbital solutions for four close binary systems: SW Lyn, QW Gem, AP Leo and V2150 Cyg. The photometric data are new, while the spectroscopy has been recently obtained within the radial velocity programme at the David Dunlap Observatory. This paper is the first in the planned series of investigations. We give an extensive description of the motivation for the series and of the main assumptions made in our solutions. The four targets of this investigation span a range of typical configurations and thus present different levels of difficulty for the combined spectroscopic and photometric orbital solutions.
Keywords: binaries: close; binaries: contact; binaries: eclipsing; stars: fundamental parameters